Drug Delivery Systems for Dental Applications - Ficai, Denisa; Sandulescu, Mihai; Ficai, Anton; Andronescu, Ecaterina; Yetmez, Mehmet; B. Agrali, Omer; Elemek, Eser; Gunduz, Oguzhan; M. Sahin, Yesim; N. Oktar, Faik (Current Organic Chemistry, 2017)
Inevitable caries formation and other tooth related diseases are one of the most common factors affecting human quality of life, as they are often followed by loss of teeth. Significant research efforts have been devoted to establishing control and preventive solutions. It is clearly known that fluoride is one of the promising chemical substances with anti-carious activity. The elimination of the microbial infection, especially the multispecies infections induced by aerobic and anaerobic bacteria, is a current challenge of the endodontic therapy. Using antibiotics or other active agents (from ions, nanoparticles to natural products) loaded in specific drug carrier systems seems to be ideal approach in treating and controlling dental diseases, even if, the drug delivery systems used in dental applications are less established comparing with other tissues/organs. Based on the importance of biomedical drug delivery systems the present study aims to give a brief review on the improvements of drug delivery systems for dental applications.
Keywords: drug delivery system